2015
DOI: 10.2135/cropsci2014.01.0080
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTL, Selection Differentials, and the Effect of Rht‐B1 under Organic and Conventionally Managed Systems in the Attila × CDC Go Spring Wheat Mapping Population

Abstract: 1129 RESEARCH M any wheat (Triticum aestivum L.) breeding objectives for organically managed systems (including grain yield, resistance to abiotic and biotic stresses, and baking quality) are similar to conventionally managed systems. It may be, however, necessary to test the expression of these traits under low input, very weedy organic conditions to maximize gain from selection in organic environments. A few traits relevant to high input farming may have negative effects on organic lands. The breeding for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(67 citation statements)
references
References 63 publications
7
59
1
Order By: Relevance
“…Ceccarelli and Grando (1991) have reported that the best lines selected in low-yield environments outperform superior lines selected in high-yield environments. In addition, the indirect selection efficiency of superior genotypes is trait dependent, and indirect selection can lead to greater genetic gains than direct selection for highly heritable traits (Hill et al 1998;Asif et al 2015). In this study, the Spearman's rank correlation coefficient between the treatments for TKW was second to that for KL among the 11 traits investigated (Table 2; Fig.…”
Section: Would Indirect Selection Of Superior Genotypes Under Normal mentioning
confidence: 59%
See 3 more Smart Citations
“…Ceccarelli and Grando (1991) have reported that the best lines selected in low-yield environments outperform superior lines selected in high-yield environments. In addition, the indirect selection efficiency of superior genotypes is trait dependent, and indirect selection can lead to greater genetic gains than direct selection for highly heritable traits (Hill et al 1998;Asif et al 2015). In this study, the Spearman's rank correlation coefficient between the treatments for TKW was second to that for KL among the 11 traits investigated (Table 2; Fig.…”
Section: Would Indirect Selection Of Superior Genotypes Under Normal mentioning
confidence: 59%
“…QKh-2D.1 and QTw-2D might have been identified due to the presence of other linked genes. The Rht-B1 gene is associated with physiological processes that affect not only plant height but also yield, grain quality, seedling vigor and adaptability to adverse environments (Fischer and Stockman 1986;Gooding et al 1999Gooding et al , 2012McCartney et al 2006;Zheng et al 2010;Bai et al 2013;Zhang et al 2013;Asif et al 2015). This study indicated that Rht-B1b had negative effects on TKW, KW, KDR, TW, DT, and ZEL.…”
Section: Novel Stable Qtls and Qtl Co-segregation With Known Genesmentioning
confidence: 79%
See 2 more Smart Citations
“…However extensive gene mapping and identification of valuable quantitative trait loci (QTL) are required, which is mostly available for major crops. Asif et al [137] recently determined that most QTLs in wheat were developed specifically to either conventional or organic management environments and that some loci did not respond similarly under different environmental pressures. This method of selection has demonstrated great success when building pest resistance through gene pyramiding for conventional systems.…”
Section: Breeding Strategies For Organic Systemsmentioning
confidence: 99%